Utilization of Family Planning Methods and associated factors among women of reproductive age group in Sunsari, Nepal (Janaki Medical College Journal of Medical Science, 2022)
Background and objectives: Family planning not only improves women’shealth but also promotes gender equality, better child health, and education, including poverty reduction. Therefore, the objective of this study was to assess the utilization of family planning methods and associated factors in Sunsari, Nepal.Materials and methods: A cross-sectional analytical study was conducted among women of the reproductive age group (15-49 years) in Sunsari in 2020. Non-probability purposive sampling was used to collect information from 212 respondents through face-to-face interviews using a Semi-structured interview schedule from ward no 1 of Barju rural municipality. Descriptive and inferential analysis (binary logistic regression)were used to find the association of utilization of family planning methods with selected demographic variables. All the variables with a p-value